2015
DOI: 10.1521/aeap.2015.27.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use Among Immigrant Latino Sexual Minorities: Multilevel Analysis After Respondent-Driven Sampling

Abstract: This study explored correlates of condom use within a respondent-driven sample of 190 Spanish-speaking immigrant Latino sexual minorities, including gay and bisexual men, other men who have sex with men (MSM), and transgender person, in North Carolina. Five analytic approaches for modeling data collected using respondent-driven sampling (RDS) were compared. Across most approaches, knowledge of HIV and sexually transmitted infections (STIs) and increased condom use self-efficacy predicted consistent condom use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…The subtheme of homophobia has a long history among Black and Latino communities and has been shown to affect HIV prevention efforts ( Brooks et al, 2005 ; Huebner, Davis, Nemeroff, & Aiken, 2002 ; Mizuno et al, 2015 ; Rhodes & McCoy, 2015 ; Stokes & Peterson, 1998 ). Many participants stated that they had to “negotiate identities” between being a Black or Latino man and being openly gay.…”
Section: Discussionmentioning
confidence: 99%
“…The subtheme of homophobia has a long history among Black and Latino communities and has been shown to affect HIV prevention efforts ( Brooks et al, 2005 ; Huebner, Davis, Nemeroff, & Aiken, 2002 ; Mizuno et al, 2015 ; Rhodes & McCoy, 2015 ; Stokes & Peterson, 1998 ). Many participants stated that they had to “negotiate identities” between being a Black or Latino man and being openly gay.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we were preparing for the implementation of two interventions to promote sexual health among Latino sexual minorities, we realized that our interventions did not acknowledge and address the contexts and concerns of transgender persons despite substantial percentages of transgender persons participating in our previous studies (Rhodes et al, 2010; Rhodes et al, 2011; Rhodes et al, 2012). For example, in a respondent-driven sampling study of Latino sexual and gender minorities, 16% of the sample self-identified as transgender (Rhodes & McCoy, 2015; Rhodes et al, 2012). Intervention curricula, materials, and logos focused on gay and bisexual men and other MSM, not transgender persons.…”
Section: Methodsmentioning
confidence: 99%
“…Economic disruption, psychological stress, population mobility and displacement, trauma and physical violence, and military activity associated with migration are risk factors for HIV transmission [15,16]. Untreated substance use and mental health problems can affect the perceived risk for HIV acquisition and promote high-risk behaviors such as sexual concurrency, unprotected anal intercourse, and injection drug use (IDU) [17][18][19].…”
Section: Introductionmentioning
confidence: 99%